Using multiple variables decision-making analysis for ERP selection. (29th May 2009) - Wu, Jen-Her; Tai, Wei-Chun; Tsai, Ray J.; Lu, Iuan-Yuan
Enterprise Resource Planning (ERP) systems have been recognised as excellent tools for integrating information, reducing operational costs and enhancing competitiveness. However, they are expensive and complex software with a well-documented high risk of failure when implemented badly. The selection of an ERP system is therefore critical. This paper identifies a set of evaluating variables within three categories: supplier, product functionality and technical capacity. These variables were based on an extensive literature review and interviews with industry experts. ELECTRE I, a multiple variables decision-making method, may then be applied for pair-wise comparison of alternatives to provide an efficient and effective method for selecting an optimum ERP system for a given situation.